New 20-cm Radio-Continuum Study of the Small Magellanic Cloud: Part I - Images - Payne J. L.; Galvin, T.; Wong, G. F.; Draskovic, D.; De Horta, A. Y.; Crawford, E. J.; Filipovic, M. D. (Serbian Astronomical Journal, 2011)
We present and discuss new high-sensitivity and resolution radio-continuum images of the Small Magellanic Cloud (SMC) at $lambda$=20~cm($u$=1.4~GHz). The new images were created by merging 20-cm radio-continuum archival data, from the Australian Telescope Compact Array and the Parkes radio-telescope. Our images span from $sim$10arcsec to $sim$150arcsec in resolution and sensitivity of r.m.s.$geq$0.5~mJy/beam. These images will be used in future studies of the SMC's intrinsic sources and its overall extended structure.